Insulin Sensitivity and Hemostatic Factors in Clinically Healthy 58-year-old Men - Agewall, Stefan; Bokemark, Lena; Wikstrand, John; Lindahl, Anders; Fagerberg, Björn (Thrombosis and Haemostasis, 2000)
The objective of this cross-sectional study was to investigate the relationship between factors of the coagulation- and fibrinolysis systems and insulin sensitivity in 104 clinically healthy, 58-years-old men. Insulin sensitivity (hyperinsulinemic euglycemic clamp) adjusted for lean body mass, the metabolic syndrome according to a suggested definition, and different factors in the coagulation- and fibrinolysis system were determined. Subjects with the metabolic syndrome were characterised by increases in PAI-1 activity, tPA antigen, protein C and protein S and low concentrations of tPA activity. Insulin sensitivity was independently and reversibly associated with PAI-1 (p = 0.014) and directly with tPA activity (p = 0.001). Insulin sensitivity was also significantly negatively associated with protein S and protein C and several components in the metabolic syndrome, however not remaining significant in multivariate analyses. Protein C and protein S were significantly associated with PAI-1 activity, tPA activity (negatively), tPA antigen and antithrombin III. In conclusion, the data indicated that insulin resistance and several of the clustering components in the metabolic syndrome are accompanied by increased plasma concentrations of the anticoagulatory proteins C and S which may represent a mechanism which counteracts the concomitantly occurring hypofibrinolysis.
Keywords: Insulin sensitivity; plasminogen activator inhibitor activity; protein C; protein S; tissue plasminogen activator